OP0317-PARE An independent review of people with rheumatoid arthritis (RA) and their caregiver's lost work time. (15th June 2017) - Bosworth, A; Jacklin, C; Burke, T; Rose, A; Jacob, I; Verstappen, S
Abstract : Background: The National Rheumatoid Arthritis Society (NRAS) is the only patient-led charity in the UK focussing specifically on rheumatoid arthritis (RA) with the key responsibility of raising awareness of the impact and burden of RA. There is a lack of information about the costs and impact of RA on work in the European community; in particular the wider societal costs such as people with RA not being able to perform their job to their best ability, losing days of work due to their RA condition, and the domino effect on caregiver employment. Objectives: To quantify the burden of RA not only on the healthcare system, but also the wider societal costs associated with RA. Methods: In 2016 NRAS undertook a partnership with the University of Chester's commercial economics partner HCD Economics who conducted the multinational Burden of Rheumatoid Arthritis: Socioeconomic Survey (BRASS). The study used a bottom-up approach to quantify the burden of disease for people living with RA across 10 European countries including France, Germany, Italy, Spain, Denmark, Sweden, Hungary, Poland, Romania and the UK. The study collected information from patients and physicians on factors associated with managing RA, plus RA sufferers' views on life and workplace impact. It collected information on the resource use and cost of patient care including treatment costs, hospitalisation, tests, and examinations. The wider societal costs included; cost of travel to appointments, requirements for aids/equipment, informal care (non-professional), ability in employment, early retirement due to RA. Work time missed, work and activity impairment were measured using the Work Productivity and Activity Impairment (WPAI) questionnaire. Results: Voluntary data were collected from 1782 patient forms, of which the average age was 55 years, 1274 (71%) were female and 833 (48%) were currently in work. This study found, on average, persons with RA lose one day of every 4 working days due to not being able to perform their job to their best ability, and completely miss 7% of work time over a 7 day period due to their RA (sample n of 646). In addition to not being able to perform their job to their best ability, almost a third of working persons with RA also had impairment in daily living activities such as shopping and work around the house (sample n of 735). This study also found family/friends have to care for 16% of RA sufferers. This care resulted in reduced employment or inability to work for 25% of family/friend caregivers (sample n of 121). Conclusions: This study highlights the impact RA has on working life amongst both those with the condition and those providing support. It is hoped these metrics will allow the conversation to open and develop with employers and government on how adapting the workplace can increase productivity. Further research should also be undertaken on the economic impact both to the individuals, their carers and society. Acknowledgements: The BRASS study was supported by unrestricted research grants from Eli Lilly and Pfizer. The study was approved by the University of Chester Ethics Committee. Disclosure of Interest: None declared